Przemowa z okazji nadania godności doktora honoris causa Uniwersytetu Śląskiego w Katowicach, 23 października 2018 roku - Coetzee, John Maxwell; Pawlicki, Marek (Śląskie Studia Polonistyczne, 2020)
The presented text is the verbatim record of the address delivered on 23rd of October 2018 by John Maxwell Coetzee on the occasion of conferring on him a title of doctor honoris causa by the University of Silesia in Katowice. The theme of the speech in question is the significance of the English language in contemporary world.